An environmental assessment of grass-based dairy production in the northeastern United States. (September 2020) - Rotz, C. Alan; Holly, Michael; de Long, Aaron; Egan, Franklin; Kleinman, Peter J.A.
Abstract: Demand for grass-based dairy production, which relies heavily on grazing and use of forage crops, is growing in the United States, primarily due to reported human health benefits of the milk produced as well as perceived environmental and animal welfare benefits. We used a whole-farm model to evaluate environmental footprints of all-grass, grass supplemented with grain, and confinement dairy production systems in the temperate climate of the northeastern U.S. Model results were depicted per unit of farmland and per unit of milk produced to provide alternate perspectives from the viewpoint of land management and commodity production. For most environmental indicators, the grass-based systems had smaller environmental impacts per unit of farmland but larger impacts per unit of milk produced compared to confinement fed systems. To verify the simulation of grass-based operations, eight dairy farms - ranging from herds that were grazed and fed only forage to herds that received some grain supplementation - were surveyed and modeled. Due to variation in climate, soil characteristics and management practices, a comparison of the two grass-based farm types showed no significant differences in environmental impacts. Farms of the same size using each production strategy along with a more traditional confinement production system were then simulated using the same climate and soil conditions for a better comparison. Predicted nitrogen and phosphorus losses to the environment, fossil energy use, water use, and greenhouse gas emissions were less from the grass-based farms compared to the confinement operation. Due to lower milk production on the grass-based dairies, nutrient losses and greenhouse gas emissions expressed per unit of milk produced were generally greater than those of the confinement system. Within the grass-based dairy systems, the system that supplemented with grain had slightly lower nitrogen and phosphorus losses per unit of farmland compared to the grass-only system, and much lower losses and emissions when expressed per unit of milk produced. Total production cost was less for the all-grass dairy than the grass with grain dairy. With a greater milk price, the all-grass system provided greater profitability per unit of land used and per unit of milk produced compared to the confinement farm of similar size. These data indicate that grass-based dairy farms can provide environmental benefits to a local watershed, but due to a lower efficiency in milk production, they may increase the aggregate environmental impacts of regional and global supply chains. Highlights: Environmental footprints of grass-based and traditional dairy farms were compared. Information from eight grass-based dairy farms was used to support model analyses. For most indicators, grass-based systems had smaller impacts per unit of farmland. Grass-based systems had greater environmental intensities per unit of milk produced. Environmental metrics of importance vary between regional and global goals.